DON’T WORRY TO MAKE A MISTAKE IN LEARNING ENGLISH - Dini Deswarni (Al-Manar : English and Arabic Journal, 2014)
Many students assumed that English is difficult, which caused by many factors such as the students’ inadequacy in order to master English. Many assumptions and negative-suggestions was affected by their environment and internal factors that has negative experiences in learning English. Fear of making mistakes is one of the factors that break their motivation in learning English, where English language is a foreign language that has any probabilities on the occurrence of making mistakes. Every mistake made, is the process to know the truth.